Ensino de Filosofia no Colégio Municipal Pelotense: uma análise histórica e crítica da disciplina de filosofia de 1960 a 2008 - Corrêa, Letícia Maria Passos (2012)
This paper describes the teaching of Philosophy from the 1960's to 2008 at Pelotense High School. The study makes a qualitative analysis of Philosophy teaching processes at this institution by means of documentation research and interviews. The text has been divided into two parts. The first one deals with the boundaries and outlines of the thesis by describing my professional path, and includes a literature review of the issues in question as well as the methodological and theoretical procedures used to implement the research. Aspects referring to criticality and the historical-critical outlook in the teaching of Philosophy are mentioned. In the second part of the study, data collected both at Pelotense High School and interviews with the teaching staff are researched. The first chapter addresses the teaching of Philosophy at Pelotense High School from 1960 to the year of the military coup d état in Brazil in 1964. Following, the 1964 1972 period is discussed. The third chapter extends from 1972 to 1985, the year of Brazilian redemocratization. The chapter that follows includes the 1985 2000 period and focuses on the Philosophy teaching reintegration into the school curriculum. The last chapter presents the teaching of philosophy at Pelotense High School between 2000 and 2008, on which occasion the teaching of Philosophy and Sociology at secondary school level became compulsory. This research aimed to understand the role of Philosophy teaching at the institution and its potential for shaping critical awareness, and concluded that Pelotense High School has been innovative in the teaching of this Course